2018
DOI: 10.4034/pboci.2018.181.95
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Access to Dental Treatment for People with Physical Disabilities in a Brazilian Metropolis

Abstract: Objective: To evaluate the barriers for accessing dental care for people with physical disabilities. Material and Methods: A cross-sectional study with 191 caregivers of individuals with physical disabilities attending a rehabilitation center in São Paulo, who responded to a questionnaire about information related to barriers (user, caregiver, government and professional) found in dental treatment, visit to the dentist and age of the first dental appointment. Data were collected from medical records regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Approximately one-third of the respondents indicated that accessibility was a major challenge, specifically the distance to the clinical facilities, cost of transportation, and lack of transport. This is in keeping with the work of de Gutierrez et al, who suggested certain patients with special needs, such as those with cerebral palsy, report greater physical barriers in accessing dental care [17]. de Gutierrez, however, did not find transportation to be a major barrier to accessing dental care by patients with special needs [17].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Approximately one-third of the respondents indicated that accessibility was a major challenge, specifically the distance to the clinical facilities, cost of transportation, and lack of transport. This is in keeping with the work of de Gutierrez et al, who suggested certain patients with special needs, such as those with cerebral palsy, report greater physical barriers in accessing dental care [17]. de Gutierrez, however, did not find transportation to be a major barrier to accessing dental care by patients with special needs [17].…”
Section: Discussionsupporting
confidence: 84%
“…This is in keeping with the work of de Gutierrez et al, who suggested certain patients with special needs, such as those with cerebral palsy, report greater physical barriers in accessing dental care [17]. de Gutierrez, however, did not find transportation to be a major barrier to accessing dental care by patients with special needs [17].…”
Section: Discussionsupporting
confidence: 84%
“…Scientific evidence shows that not all dentists are able to identify different groups with special needs, which may constitute one of the barriers to access to dental treatment. The number of universities that include the PSN discipline in their undergraduate and graduate programs is still small considering the need in Brazil [15,16,20].…”
Section: Resultsmentioning
confidence: 99%
“…Professional qualification is fundamental in improving PD's oral health 30 and was pointed out by caregivers as a barrier to access care. 31 Thus, these professionals must receive continuing education to qualify and increase confidence in the specialty's practice. 32 The CEO's provision of dental care to PD is mandatory, and there is a decrease in professionals with a postgraduate degree or specialized in this user profile, already observed in Brazilian studies.…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of specialists may explain the increase in professionals without specific training to work with PDs. Professional qualification is fundamental in improving PD’s oral health 30 and was pointed out by caregivers as a barrier to access care 31 32 …”
Section: Discussionmentioning
confidence: 99%